(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical, subclinical characteristics and antibiotic resistance of bacterial co-infection in children with pneumonia caused by Respiratory Syncytial Virus (RSV) at the Vietnam National Children’s Hospital. Subjects and Methods: A descriptive study conducted on cases of pneumonia due to RSV and bacterial co-infection at the Center for Pulmonology and Respiratory Care, Vietnam National Children’s Hospital. Results: Among the 162 children, 58.6% were male and 41.4% were female. The majority were under 12 months old (68.9%). The most common clinical symptoms were fever (74.7%) and respiratory failure (66.7%). Subclinical tests (X-ray, hematological blood tests, CRP) clearly reflected the level of infection. The prevalence for beta-lactamases producing H. influenzae was high (72,13%) and Haemophilus influenzae showed high resistance to Ampicillin, Cefuroxime, and Cefaclor (>90%). Cefotaxime exhibited a high sensitivity rate (98.2%), and the bacteria were not resistant to Ceftriaxone, Imipenem, and Ciprofloxacin. Conclusion: Children with RSV pneumonia commonly present with typical clinical signs such as fever, respiratory failure, and lung rales. Subclinical tests indicate significant infection. H. influenzae is the most common co-infected bacteria with a high resistance rate to many antibiotics, requiring caution in choosing antibiotics for treatment.